Pelaksanaan Skrining Kesehatan sebagai Upaya Mencegah Penyakit Tidak Menular pada Usia Produktif dan Lansia di Negeri Latuhalat - Laury M. Ch. Huwae; Prezto S. A. Dabutar; Glaselaria A. Oeijano; Clifford R. Kundiman; Alia U. Mahua; Ronald D. Hukubun (Universitas Maritim AMNI Semarang, 2023)
The enhancement number of incident non-infectious disease (PTM) is created through the implementation of non-infectious disease health screening and education presentation, especially for the society of Negeri Latuhalat in productive age and elders. This activity is conducted from house to house or door to door. The method that has been utilized is screening implementation also the presentation of education about the non-infectious disease in the society of Negeri Latuhalat. The steps that have been used during the activity are: planning and preparation, health checkup, also the presentation of education. The result of the screening pursuit towards non-infectious disease obtains average participant with stomach circumference above common, there are 55%, IMT overweight 45%, IMT obesity rate I 15%, hypertension 55%, diabetes 15%, high-uric acid 45%, total cholesterol 45%. Therefore, it is needed to provide education for the society of Negeri Latuhalat in allied with the changes in lifestyle for preventing the enhancement number of non-infectious diseases, particularly in productive age and elders.